Impact of climate change on child outcomes: an evidence gap map review - Parveen Ali; Megan Kennedy; Zohra S Lassi; Yared Asmare Aynalem; Bukola Salami; Lydia Aziato; Solina Richter; Salima Meherali; Samuel Adjorlolo; Saba Un Nisa; Kênia Lara Silva (BMJ Publishing Group, 2024)
Background Climate change and extreme weather events significantly threaten neonatal and child health. This review aims to provide a comprehensive overview of the current evidence on the impact of climate change on child health, using the evidence gap map (EGM) to address knowledge gaps and establish a foundation for evidence-based interventions and future research.Method From inception, academic databases (such as MEDLINE, EMBASE, Global Health, CINAHL and Scopus) and grey literature were systematically searched. We included climate change-related studies involving children aged 0-5 worldwide. Covidence facilitated a rigorous screening process, and we conducted a critical appraisal. Two independent reviewers handled screening and data extraction. Eligible studies underwent coding and extraction using Evidence for Policy and Practice Information (EPPI) reviewer software. The EGM was constructed using EPPI Mapper, and comprehensive findings were presented through live links and figures.Result We identified 196 studies, comprising 59.2% children and 40.8% neonates, with diverse research approaches, including 94% quantitative studies. There has been a notable increase in research publications over the past 5 years. Evidence is heavily concentrated in Asia (93 studies) and Africa (47 studies). The most frequently studied exposures are those related to extreme climate events, followed by drought and floods. However, there are gaps in the study of extreme cold and storms. The significant outcomes comprised preterm birth (55 studies), low birth weight (27 studies), malnutrition (59 studies) and diarrhoeal diseases (28 studies). Evidence on mental health problems and congenital disabilities receives relatively less attention.Conclusion This EGM is crucial for researchers, policymakers and practitioners. It highlights knowledge gaps and guides future research to address the evolving threats of climate change to global child health.Trial registration number INPLASY202370086